Predicting the equity market with option implied variables - Marcel Prokopczuk; Björn Tharann; Chardin Wese Simen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
We comprehensively analyze the predictive power of several option implied variables for monthly S & P 500 excess returns and realized variance. The correlation risk premium (CRP) emerges as a strong predictor of both excess returns and realized variance. This is true both in- and out-of-sample. A timing strategy based on the CRP leads to utility gains of more than 4.63% per annum. In contrast, the variance risk premium (VRP), which strongly predicts excess returns, does not lead to economic gains.
Keywords: G10; G11; G17; 330; Equity Premium; Option Implied Information; Portfolio Choice; Predictability; Timing Strategies